Regulation of mergers by the UK competition authorities: the effects on shareholder value and management motivations for mergers - Arnold, Malcolm F. (Cranfield University, 2007)
The UK competition authorities are responsible for regulating company mergers that were originally considered to have adverse effects that were “against the public interest”, or presently that could result in a “substantial lessening of competition”. The research in this thesis examines wider economic side effects of this regulatory policy that fall outside the remit of the competition authorities. Data on 63 merger cases that were subject to the merger regulatory process by the UK competition authorities between 1989 and 2002 are studied for effects on two economic aspects, shareholder value and managers’ motivations to undertake mergers. Some previous studies have suggested that competition regimes can destroy shareholder value. The research in this thesis confirms the finding from earlier studies of greater gains to shareholders in target rather than bidding companies, but does not find evidence supporting overall loss of shareholder value to target company shareholders when a merger is prohibited. It finds evidence that when the regulatory regime is stable and well understood the capital market behaves efficiently in response to new information. However, for a sub group of the mergers involving companies with a new regulatory regime, of which industry and the market had little or no experience with respect to mergers, the capital market operated less efficiently. A number of studies have also considered the motivation of managers to follow a merger strategy. Apparently, none has looked at the influence of competition regulation on merger motives using stock market data and event study techniques. This research examined data for the stock market’s perceptions of what motivated managers to pursue their initial merger bid. The findings suggest that Synergy and Hubris dominate as motivations for mergers and that, unintentionally, competition policy may help to reduce the number of mergers motivated by Managerialism.
Keywords: Competition policy; Event study; Privatised industries; Synergy; Hubris; Managerilism